The role of the amygdala in emotional experience during retrieval of personal memories. Issue 10 (26th November 2019) - Ford, Jaclyn H.; Kensinger, Elizabeth A.
ABSTRACT: Although the role of the amygdala in emotional memory retrieval has long been established, how such engagement varies depending on valence and retrieval context is less clearly understood. Participants retrieved personal memories associated with primarily positive, primarily negative, and mixed-valence images, pressing a button when successful. The button press divided trials into search and elaboration phases. Participants provided positivity and negativity ratings immediately following each trial, and then again in a post-retrieval survey . The relation between amygdala recruitment and emotionality exhibited a four-way interaction, with no other significant main effects or interactions. The interaction was driven by a temporal shift in the role of amygdala recruitment during retrieval of memories associated with mixed-valence images: Negativity ratings were supported more by search-related activity whereas positivity was more strongly associated with elaboration. Amygdala activity during retrieval relates to emotional experience in more complicated ways than previously understood. When participants were able to consider positive and negative aspects of the same event, amygdala recruitment during search and elaboration were associated with opposite behavioural effects. Such findings suggest that the amygdala may support distinct aspects of emotional experience for the same memory depending on when during retrieval it is recruited.